Establishing sustainable consumption: how future policies can channel consumer preferences - Henkel, Joshua; Schwesinger, Georg (Bremen papers on economics & innovation, 2020)
This paper relates cultural evolution theory and social learning dynamics to induced preference change in consumption behavior. We argue that the promotion of sustainable consumption via preference change is a cornerstone of future policy and should complement standard regimentations such as regulation for harm reduction in production and the investment in green technologies. The application of cultural evolution mechanisms may act as a key element for implementing future societal acceptance of responsible individual consumption and a trigger for the self-transformation of the economy. We will discuss what kind of policies can be used in future to channel our consumption preferences and build up an economic “presents for the future” scenario that will go beyond existing policy tools. An already established tool in behavioral economics that provides an elegant, cheap and often effective measure to promote green behavior is “green nudging.” However, it comes at the cost of being perceived as paternalistic and non-transparent. In addition, nudging requires the alteration of a very specific choice architecture for every single consumption decision scenario and is therefore limited in its scope of application and - most importantly - long-term effectiveness. Here we offer a more general behavioral approach for future environmental policy. We argue that preference change for consumption can be induced by policy makers using tools drawn from cultural evolution. We develop concrete scenarios for policy makers to induce pro-environmental preferences within consumer populations. We argue that our approach is likely to induce alteration of existing and the establishment of new consumption patterns on a much larger scale than nudging and will be more successful in establishing permanent future effects.